Pilonidal sinus surgery: could we predict postoperative complications?. Issue 3 (3rd June 2014) - Milone, Marco; Di Minno, Matteo ND; Bianco, Paolo; Coretti, Guido; Musella, Mario; Milone, Francesco
Abstract: Pilonidal sinus surgery could, as of now, be considered a surgery tailored more to the surgeon than to the patient. In an attempt to give to surgeons an objective instrument of decision, we have evaluated which variables could be considered predictive of postoperative complications after pilonidal sinus surgery. A prospective electronic database of all patients treated for sacrococcygeal pilonidal disease was analysed. Sex, age, obesity, smoking, recurrent disease, the presence of multiple orifices and the distance between the most lateral orifice and midline were recorded and correlated with the occurrence of postoperative complications (infection and recurrence); 1006 patients were evaluated. Excision with primary mid‐line closure was performed on all the patients. Mean follow‐up was 7·3 ± 3·6 years. A total of 158 patients with postoperative complications (infection and/or recurrence) were recorded during this period. A multivariate analysis showed that, after adjusting for major clinical and demographic characteristics, only a recurrent disease [odds ratio (OR): 3·41, 95% confidence interval (CI): 1·89–6·15, P < 0·001] and the distance of lateral orifice from midline (OR: 26·3, 95% CI: 12·2–56·7, P < 0·001) were independent predictors of overall postoperative complications. Focussing on the distance from midline, the receiver operative characteristic (ROC) analysis showed that the distance of lateral orifice from midline predicted 79·2% of complications and the Youden's test identified the best cut‐off as 2·0 cm for this variable. An evidence‐based tool for deciding on the type of surgical intervention could be developed and validated by further ad hoc prospective studies evaluating our results in comparison to other different types of surgical techniques. Our results support the use of these variables as an effective way to tailor pilonidal sinus surgery to the patient, so as to obtain the best results in patient care.